Simultaneous transistor pairing and placement for CMOS standard cells - Ang Lu; Hsueh-Ju Lu; En-Jang Jang; Yu-Po Lin; Chun-Hsiang Hung; Chun-Chih Chuang; Rung-Bin Lin (2015 Design, Automation & Test in Europe Conference & Exhibition (DATE), 2015)
This paper presents an integer linear programming approach to transistor placement problem for CMOS standard cells with objectives of minimizing cell width, wiring density, wiring length, diffusion contour roughness, and misalignments of common ploy gates. Our approach considers transistor pairing and transistor placement simultaneously. It can achieve a smaller number of transistor chains than the well-known bipartite approach. About 31% of the 185 cells created by it have smaller widths and no cells whose widths are larger than their handcrafted counterparts.